Apparent digestibility of dry matter, crude protein, and amino acids of six rendered by-products in juvenile Litopenaeus vannamei - Villarreal Cavazos, David Alonso; Ricque Marie, Denis; Peña Rodríguez, Alberto; Nieto López, Martha Guadalupe; Tapia Salazar, Mireya; Lemme, Andreas; Gamboa Delgado, Julián; Cruz Suárez, Lucía Elizabeth (Universidad Autónoma de Baja California, Instituto de Investigaciones Oceanológicas, 2014)
Apparent digestibility coefficients (ADC) of dry matter, crude protein (CP), and amino acids (AA) were evaluated in diets with six rendered by-products used to feed juvenile Pacific white shrimp: two poultry meals (poultry meal 1, 69% CP; poultry meal 2, 72% CP), two feather meals (89% CP), one blood meal (96% CP), and one pork meal (57% CP). Experimental diets were formulated with 30% of the test ingredient and 70% of a commercial diet supplemented with 1% of chromium oxide as inert marker. AA contents in ingredients, diets, leached diets, and feces were determined by high performance liquid chromatography. Preprandial AA losses attributed to leaching were higher in the blood meal diet (15%) and pork meal diet (10%). Poultry meal diets 1 and 2 showed mean AA losses of 3% and 5%, respectively, while the reference diet had a mean AA leaching of 6%. The AA that had the highest leaching rates were lysine (21%), methionine (15%), and histidine (12%). The ADC of dry matter was higher for poultry meals 1 (70%) and 2 (73%), followed by pork meal (69%), feather meals (61%), and blood meal (57%). The digestibility of CP was higher for poultry meals (78–80%), followed by pork meal (76%), and blood meal and feather meals (65–67%). The digestibility of CP in the reference diet (83%) was higher than that observed for all the animal by-product meals except the poultry meals. The ADC of the sum of AA adjusted for nutrient leaching fluctuated from 65% for blood meal to 80% for poultry meals.